Modernizing the Otolaryngology Referral Workflow: The Impact of Electronic Consultation. (15th December 2020) - Kinberg, Eliezer C.; Kirke, Diana N.; Trosman, Samuel J.
Abstract : Objectives/Hypothesis: To determine the impact of electronic consultation on the otolaryngology clinic workflow at our high‐volume public hospital. Study Design: Retrospective Observational Study. Methods: This is a retrospective observational analysis study. Operational data regarding clinic volume, referral patterns, and scheduling efficiency were assessed over a 9‐month period in 2018 prior to implementation of electronic consultation. The same data were collected for the 9‐month period immediately following implementation of electronic consultation in 2019. Results: During the pre‐implementation (pre‐EC) period, 3, 243 otolaryngology referrals were made as compared to 4, 249 post‐implementation (post‐EC). 86% of referrals were scheduled for a clinic appointment pre‐EC, compared to 61% post‐EC ( P < .00001) 24.5% of patients were evaluated within 30 days pre‐EC compared to 53.6% post‐EC ( P < .00001). The average time to be seen by an otolaryngology provider declined from 60.8 days pre‐EC to 42.8 days post‐EC ( P = .0029). There was a 50% decline in the percentage of appointments canceled by patients in the post‐EC period as compared to pre‐EC. Conclusions: In our experience, implementation of electronic consultation significantly reduced both wait times for a clinic appointment and the percentage of no‐show or canceled appointments. Electronic consultation may be a valuable tool in improving the efficiency and yield of the modern otolaryngology clinic. Level of Evidence: 4 Laryngoscope, 131:E1792–E1796, 2021